Alfred Easton Poor papers - Poor, Alfred Easton, 1899-1988.
Correspondence, writings, logbooks, subject files, publications, reports, appointment calendars, sketchbooks, photographs, and other papers pertaining primarily to Poor's architectural career, particularly his designs for public buildings. Includes materials relating to designs for the Wright Brothers Memorial in Kitty Hawk, N.C., and the Library of Congress James Madison Memorial Building in Washington, D.C., to the restoration of the West Front and renovation of the old Supreme Court chamber of the U.S. Capitol, and to his activities as an official with the National Academy of Design. Also includes materials related to his naval service during World War I and his command of the U.S. Naval Reserve during World War II.
Library of Congress Prints and Photographs Division.
Architect and U.S. naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Naval Reserve; United States. -- Navy -- Officers; Library of Congress James Madison Memorial Building (Washington, D.C.); National Academy of Design (U.S.); United States Capitol (Washington, D.C.); Architecture -- Washington (D.C.); Library buildings -- Washington (D.C.); Memorials -- North Carolina; Public buildings -- United States; World War, 1914-1918 -- Naval operations, American; World War, 1939-1945 -- Naval operations, American; United States -- Capital and capitol; Wright Brothers National Memorial (N.C.); Architects; Naval officers